Pengaruh Motivasi, Kompensasi dan Budaya Kerja Terhadap Kinerja Penyuluh Pertanian di Kabupaten Ogan Ilir Provinsi Sumatera Selatan - Lamella Nintha Pinem; Luis Marnisah (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This study aims to analyze and demonstrate the Influence of Motivation, Compensation, and Work Culture on the Performance of Agricultural Extension Workers in Ogan Ilir Regency. The methods used in this study are descriptive analysis, classical assumption tests, and multiple linear regression. The results of this study are as follows: (1) Motivation of agricultural extension workers has a positive and significant effect on their performance with a t value of 2.273 > t table 1.653. This motivation enhances the performance of agricultural extension workers when they independently complete their tasks and responsibilities. (2) Compensation has a positive and significant effect on the performance of agricultural extension workers with a t value of 3.435 > t table 1.653. Timely payment of wages or salaries by the institution enhances the performance of agricultural extension workers in independently completing their tasks and responsibilities. (3) Compensation also has a positive and significant effect on the performance of agricultural extension workers with a t value of 3.872 > t table 1.653. A work culture that emphasizes readiness to take risks in responsible work also contributes to the improvement of agricultural extension workers' performance when working independently. (4) Simultaneously, motivation, compensation, and work culture have a positive and significant effect on the performance of agricultural extension workers in Ogan Ilir Regency with a significance level of 0.001 < 0.05 and an F value of 25.832 > F table 2.654. All independent variables have a positive effect on the performance of agricultural extension workers, indicating that the higher the independent variables, the higher the performance of agricultural extension workers in Ogan Ilir Regency..